Warisan pedang Rasulullah & para sahabat/ Ahmad Lutfi Abdul Wahab Al-Linggi - 594148 Ahmad Lutfi Abdul Wahab Al-Linggi author (Petaling Jaya, Sel. : Wawleed Pub., 2014)
Includes bibliographical references (pages 274-282) and index.